BILATERAL TRADE AND ECONOMIC GROWTH: THE EMPIRICAL EVIDENCE BETWEEN U.S. AND SOUTH KOREA - 강현수 (한국농촌경제연구원, 2009)
This paper analyzes the relationships between bilateral trade and economic growth in the U.S. and Korean economies. Using quarterly data from 1990 to 2008, the theoretical procedures utilize Ordinary Least Square (OLS) and Seemingly Unrelated Regression (SUR) models under the static model assumption, an Impulse Response Function (IRF) and Forecast Error Variation Decomposition (FEVD) under the Vector Autoregressive (VAR) model, and Granger causality tests. Empirical results indicate a causal relationship between bilateral export growth and economic growth for the U.S. and Korean economies. The export-led growth (ELG) hypothesis is strongly supported by the results of Granger causality tests on Korean exports.
Keywords: export-led growth; bilateral trade; Granger causality; South Korea; United States; export-led growth; bilateral trade; Granger causality; South Korea; United States